A New Species of the Simulium (Simulium) argentipes Species-Group (Diptera: Simuliidae) From Taiwan, and Its Phylogenetic Relationships With Four Related Species - Takaoka, Hiroyuki; Low, Van Lun; Tan, Tiong Kai; Huang, Yae Te; Fukuda, Masako; Ya'cob, Zubaidah (Oxford University Press, 2018)
A new black fly species, Simulium haiduanense Takaoka, Low & Huang (Diptera: Simuliidae), is described on the basis of females, males, pupae, and mature larvae from Taiwan. This new species is placed in the Simulium argentipes species-group of the subgenus Simulium (Diptera: Simuliidae) and is characterized by the yellowish female legs, ovipositor valves rounded apically and with its inner margin concave, claw with a small subbasal tooth, male style without a basal protuberance, pupal gill with eight flaments, corbicular cocoon, and larval abdomen lacking paired protuberances. It represents the first record of the S. argentipes species-group from Taiwan. Taxonomic notes are given to separate this new species from all eight species in the same species-group. The phylogenetic relationships of this new species with four related species are presented.